Theatre for audiences labelled as having profound, multiple and complex learning disabilities: assessing and addressing access to performance - Brigg, Gillian (2013)
The research described in this thesis is the result of a collaborative project between The University of Nottingham and Roundabout Education at Nottingham Playhouse, funded through an AHRC Collaborative Doctoral Award, which aimed to explore and begin to overcome the barriers to access to theatre for audiences labelled as having profound and multiple learning disabilities (PMLD). Positioned primarily from the perspective of the unique worlds of five profoundly disabled young people, the thesis begins with an assessment of their access to theatre in the light of disability discrimination legislation particularly Article 31 of the United Nations Convention on the Rights of the Child, 1991 - and highlights their disenfranchisement from past and current consultation processes, which perpetuates the lack of theatre appropriate to their needs. An initial examination of current audience reception theory - and current theatrical practice for PMLD audiences - suggests that this 'invisibility' is caused by a complex range of historico-cultural factors. The thesis describes the two practical research phases which I undertook as a key part of this collaborative project in order to address this shortfall. In the first phase, Thumbs Up, a team of specialists from a range of art forms worked alongside young people at a Nottingham School to experiment with the engagement potential of three theatre spectra (silence-sound, darkness-light and stillness-action) to foreground emotional narrative moments. This led to the second phase, White Peacock, in which I created a play using the three spectra to construct emotional narrative and utilised the concepts of inner and outer frames to ensure that those narratives could be experienced by PMLD audiences within a safe ethical framework that kept the distinction between reality and performance distinct at all times. The thesis concludes with a number of foundational principles emerging from the research that will assist theatre-makers wishing to create narrative theatre for PMLD audiences in the future.